Finite element validation of 3D American football faceguard structural stiffness models - Ferriell, W. D.; Batt, G. S.; DesJardins, J. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Despite continued efforts to improve American football headgear technology, minimal structural changes have been made to faceguard design in the past 20 years. Although each new helmet system has its own compatible faceguard series, the primary design components have changed little between helmet systems. Additionally, little is known about specific parameters that influence faceguard performance, largely due to the variation inherent in laboratory impact testing. The goal of this study was two-fold: to validate a reverse engineering method for developing a library of faceguard models; and to validate the finite element simulation of three common American football faceguards subject to a quasi-static structural stiffness test. Three common Riddell® Speedflex™ (Des Plaines, IL) faceguard styles were modeled using a novel reverse engineering approach. Within ANSYS® Mechanical™ (ANSYS, Inc., Canonsburg, PA), the faceguards were modeled as stainless steel (elastic modulus = 193 GPa, Poisson`s ratio = 0.31). A displacement of 5 mm was prescribed in the posterior (z) direction. Boundary conditions were applied to accommodate the coronal plane (x, y) translation at clip attachment locations. The computational results correlated to the experimental results with statistical significance (p value = 0.001). The Nose location was the most reliable with an average percent difference from experimental results of 2.7%, compared to 10.8% and 9.9% at the Mouth and Chin locations, respectively. Many studies utilizing computational models of protective headgear lack reported validation of headgear components. This study has validated the structural stiffness of three common faceguards to be used in future computational analyses. Furthermore, advancements in additive manufacturing technologies have opened the door to increasingly complex faceguard design capabilities; however, little is known about specific parameters that influence faceguard performance. With the models validated in this study, parameterized faceguard models should be used to iterate between design variables and assess the contribution of each variable on faceguard structural stiffness.